Macrosyntactic corpus annotation. The case of Zaar - (:unkn) unknown (My University, 2018)
This paper argues for a minimal annotation representing in a simple and concise way the interface between information structure and syntax. The article uses the concept of macrosyntax, based on illocutionary units, for a new level of annotation using existing morphosyntactic tiers in Elan. One of the main assets of this system of annotation lies in the notion of piles it uses to represent the oral discursive flow and account for dysfluencies, discontinuities and ellipses. A pilot 15,000 words corpus has been annotated in Elan to run a preliminary study of the information structure of illocutionary components in Zaar, a Chadic language spoken in Nigeria. Their micro-and macro-syntactic properties are represented using Universal Dependencies Grammar.
Keywords: African Research